Aphananthe aspera (Thunb.) Planch.: An Unexploited Eastern Asian Species from the Center of Biodiversity (Bangladesh Pharmaceutical Journal, 2022)
Aphananthe Aspera (Thunb.) Planch. is a towering woody deciduous tree and belongs to riparian forest territory. It is highly allocated to the Northern region of Eastern Asia especially Korea, China, Northern Vietnam, and Japan to be the richest countries with this species. The plants were assayed based on various types of methods including extraction. Based on folkloric usage it is important to treat acne, inflammation and cancer. Google Scholar, Web of Science, PubMed, Science Direct, and MEDLINE etc. are the electronic versions from which many bibliographic records were thoroughly explored to identify, collect, and analyze available information relevant to A. aspera. The extracted data were scrutinized in order to have a better understanding of the existing research on this species and to look into the plant's future potential in pharmaceutical research. This study aims to offer current knowledge on botany, distribution, ethnomedicinal applications, pharmacological actions, clinical study and reported phytochemicals of A. aspera. Finally, this plant is still recommended for extensive research to explore prospective novel sources of novel therapeutic agents as there are very little data available on this plant to the best of our knowledge. Extensive research on this plant can open a new horizon to discover novel therapeutics.Bangladesh Pharmaceutical Journal 25(2): 218-228, 2022 (July)